2020
DOI: 10.1186/s12974-020-01763-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 is neuroprotective in experimental pneumococcal meningitis through modulation of hippocampal DNA methylation

Abstract: Background Bacterial meningitis (BM) causes apoptotic damage to the hippocampus and homocysteine (Hcy) accumulation to neurotoxic levels in the cerebrospinal fluid of children. The Hcy pathway controls bioavailability of methyl, and its homeostasis can be modulated by vitamin B12, a cofactor of the methionine synthase enzyme. Herein, the neuroprotective potential and the underlying mode of action of vitamin B12 adjuvant therapy were assessed in an infant rat model of BM. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 66 publications
(80 reference statements)
2
15
0
1
Order By: Relevance
“…B12 supplementation has also been shown to promote DNA methylation changes and affect the antidepressant response in a mouse model [161]. Supplementation also restores hippocampal DNA methylation levels in rats with bacterial meningitis [162]. These studies suggest that B12 supplementation could be explored in scenarios where increased methylation potential is required, analogous to the FA supplementation of pregnant women to prevent NTDs.…”
Section: Targeting One-carbon Metabolism For the Treatment Of Diseasementioning
confidence: 87%
“…B12 supplementation has also been shown to promote DNA methylation changes and affect the antidepressant response in a mouse model [161]. Supplementation also restores hippocampal DNA methylation levels in rats with bacterial meningitis [162]. These studies suggest that B12 supplementation could be explored in scenarios where increased methylation potential is required, analogous to the FA supplementation of pregnant women to prevent NTDs.…”
Section: Targeting One-carbon Metabolism For the Treatment Of Diseasementioning
confidence: 87%
“…In general, DNA hypomethylation in gene promoters is associated with the activated state of their expression ( 12 ). It is already known that promoters of genes encoding cytokines are rapidly demethylated (~6 hours) after T cell activation ( 13 ) and that several genes encoding key cytokines and chemokines have increased systemic expression in patients with COVID-19 ( 14 ) are regulated by the methylation of CpGs in their promoters or enhancers ( 15 18 ). The ability of RNA viruses to hijack the epigenome of host immune cells in order to evade antiviral defense is widely acknowledged ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cobalamin (Vitamin B 12 ) contributes to the protection of nerve fibers through myelin sheath synthesis [ 171 ]. In a recent study, vitamin B 12 was experimentally demonstrated to have modulatory neuroprotective and anti-inflammatory activities against pneumococcal meningitis and hippocampus damage [ 172 ]. In addition, hippocampus apoptosis, triggered by bacterial meningitis, was diminished by vitamin B 12 treatment (10 µL intramuscular dosage) [ 172 ].…”
Section: Neuroprotective Mechanistic Narratives Of Active Principles ...mentioning
confidence: 99%